The Influence of Marketing Mix on Customer Purchasing Decision at The Abraham and Smith Restaurant - Adhiansyah, Ali; Rizkyanfi, Mochamad Whilky (Universitas Pendidikan Indonesia, 2020)
The background of this research is based on the stagnant sales data of Abraham and Smith. This study aims to determine the effect of the marketing mix on consumer buying decisions in Abraham and Smith. This research is a quantitative research, using statistical-descriptive and verificative methods of analysis, which describe and define the influence of the independent variable (X), namely the marketing mix (product, price, promotion, location, people, physical evidence, and process) on the dependent variable (Y), namely consumer buying decisions. This study employs the multiple linear regression analysis. Respondents of this study were 111 Abraham and Smith consumers, selected through accidental sampling technique. The results of this study show that the marketing mix, which has a significant effect on Abraham and Smith's consumer purchasing decisions, are product, place, and physical evidence. The conclusion of this research is that the variables of product, place, and physical evidence have a significant influence on consumer purchasing decisions. For further research, it is recommended to dig deeper into product variables, place, and physical evidence.